Keruntuhan Rezim Evo Morales di Bolivia - Muhaimin Zulhair Achsin (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2020)
This article presents a question â€œwhat are the influences of political factors on the fall of the Evo Moralesâ€™ regime in Bolivia?â€. This article aims to describe the influence of political factors on the fall of Morales' regime. This qualitative study uses the theory of regime survive and fall developed by Mainwaring and Linan. The findings are that there are three variables namely preferences, policies, and international politics that contributed to the fall of Evo Moralesâ€™ regime with the particular condition. Three premises that related to the political opposition offered by Mainwaring and Linan are also valid in this study, however political blunder has also likely contributed to the growing of political opposition.